A snapshot of the litter problem along the Viña del Mar - Concón coastal strip, Valparaíso region, Chile. (November 2020) - Rangel-Buitrago, Nelson; Barría-Herrera, José; Vergara-Cortés, Hernán; Contreras-López, Manuel; Agredano, Roberto
Abstract: Along the Viña del Mar - Concón coastal strip 11, 894 litter items were collected, and grouped into 48 different categories (11 litter typologies). The average litter abundance was 0.25 items/m 2, plastic items, and cigarette butts being the most common. Hazardous litter can be found along the entire study area, reaching 28.9% (3438 items of 11, 894 total items collected distributed in 14 different categories), and an average of 0.071 items/m 2 . The application of environmental evaluation indices based on litter data, allows categorizing the study area as a clean-moderate coastal strip with some presence of hazardous litter items, and unsatisfactory environmental conditions. Studied sectors were statistically grouped into three specific types that ranged from sectors in optimal environmental conditions (Group A) to sectors in adverse environmental conditions (Group C). The typology and magnitudes of litter found along the study area suggest a combination of sources that mainly include direct activities on the beach (recreational and smoking-related) as well dumping. In the same way, sanitary waste, ocean/waterway items, and items related to surfing activities were observed. Strategies for litter management and environmental quality improvement need to be developed and enforced. Highlights: Litter was found along Viña del Mar - Concón coastal strip with an average abundance of 0.25 items/m 2 . 48 different litter categories (11 litter typologies). Plastics and cigarette butts dominated the litter collected with an average of 66 %. The percentage of hazardous anthropogenic litter reached a value of 28.9% (3438 items of 11894 total items collected. Litter composition suggests a combination of sources that mainly include direct activities over the beach